A cross-sectional analysis of publication of pediatric global health abstracts from seven major international conferences. - Catherine Shari; Tory Prynn; Sarah Mohammedahmed Abbas; Tommy Davis; Jeesoo Lee; Gandolina Melhem; Hussein K Manji; Brittany L Murray; Richard Omore; Shayli Patel; Stephanie J Sirna; Adrianna L Westbrook; et al. (PLOS Global Public Health, 2023)
Research presented at conferences may increase context-specific evidence in low- and middle-income countries (LMICs), where global childhood disease burden is greatest and where massive relative deficits in research persist. Publication of studies presented at conferences is necessary for complete results dissemination. Our objective was to determine the frequency of publication of pediatric global health conference abstracts and to identify factors associated with publication. We conducted a cross-sectional study of abstracts that reported pediatric research conducted in at least one LMIC presented at seven major scientific conferences in 2017, 2018, and 2019. We used PubMed, EMBASE and Google Scholar to search for publications of the results presented as abstracts. We created a Kaplan-Meier curve to determine the cumulative incidence of publications and used predetermined abstract-level factors to create a multivariable Cox proportional hazard model to identify factors associated with time to publication. There were 8,105 abstracts reviewed and 1,433 (17.7%) reported pediatric research conducted in one or more LMICs. The probability of publication of pediatric global health abstracts was 33.6% (95% confidence interval [CI] 31.2-36.1%) at 24 months and 46.6% (95% CI 44.0-49.3%) at 48 months. Abstracts that reported research conducted in East Asia and Pacific (adjusted hazard ratio [aHR] 3.06, 95% CI 1.74-5.24), South Asia (aHR 2.25, 95% CI 1.30-3.91%), and upper-middle-income countries (1.50, 95% CI 1.12-2.02) were published sooner than those that reported research in LMICs in Europe and Central Asia and lower-middle-income countries, respectively. Fewer than half of pediatric global health abstracts were published in peer-reviewed journals up to four years after presentation at international conferences. Efforts are urgently needed to promote the widespread and long-lasting dissemination of pediatric research conducted in LMICs presented as abstracts to provide a more robust evidence base for both clinical care and policy related to child health.